2017
DOI: 10.1039/c7ra01511a
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous complexes supported by sterically encumbered asymmetric bis(arylimino)acenaphthene (BIAN) ligands: synthesis, characterization and screening for catalytic hydrosilylation of carbonyl compounds

Abstract: Structurally characterized Fe complexes bearing asymmetric bidentate BIAN ligands were synthesized and their use as room-temperature hydrosilylation precatalyst was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…In recent years, our group has been interested in the synthesis, characterization and reactivity of transition metal complexes supported by O‐ or N‐donor ligands with bulky CHPh 2 substituents . Thus, we herein report the double lithiation of o ‐benzhydryl phenols H 2 [ R OC] (R = H ( 1a ) or Me ( 1b )) without any additional chelating base under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has been interested in the synthesis, characterization and reactivity of transition metal complexes supported by O‐ or N‐donor ligands with bulky CHPh 2 substituents . Thus, we herein report the double lithiation of o ‐benzhydryl phenols H 2 [ R OC] (R = H ( 1a ) or Me ( 1b )) without any additional chelating base under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The signal for the phenyl protons in ligand L2 appears as a singlet due to the symmetrical nature of the molecule as a result of the rigid acenaphthene backbone which prevents rotation around the imine carbon–carbon bond and forces the imine nitrogen atoms to remain in a fixed orientation , . It has been reported that bis(N‐arylimino)acenaphthene derivatives of alpha diamine ligands are more rigid and sterically bulky compared to diimine ligands derived from glyoxal or acyclic diketones and this rigidity may impose stable chelation to metal complexes exhibiting a more limited range of bonding modes and impacting high chemical stability with respect to hydrolysis and cleaving of the central C–C bond . The IR spectra of L1 and L2 show absorption bands for the imine C=N bond at 1603 cm –1 and 1659 cm –1 and the O–H bond at 3075 cm –1 and 3289 cm –1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only one example of structurally characterized iminopyridine aluminum trihalide complex has been reported [9]. This contribution is part of our ongoing investigation on the synthesis, characterization and reactivity of earth-abundant-metal complexes supported by redox-active ligands [10,11]. The asymmetric unit of the title structure contains one Al(III) center coordinated with one α-iminopyridine ligand, as well as one CH 2 Cl 2 solvent molecule.…”
Section: Commentmentioning
confidence: 95%